2001
DOI: 10.1291/hypres.24.531
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinsulinemia for the Development of Hypertension: Data from the Hawaii-Los Angeles-Hiroshima Study.

Abstract: The present study was to assess the association of metabolic factors including hyperinsulinemia, with the development of hypertension in Japanese-Americans. One hundred forty normotensive (<140/90 mmHg) subjects aged 40 to 69 years old from the Hawaii-Los Angeles-Hiroshima study were followed for 15 years. Patients with cardiovascular disease were excluded. Body mass index (BMI), blood pressure (BP), serum total cholesterol (TC), triglycerides (TG), uric acid (UA), and glucose and insulin responses at baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 34 publications
2
51
1
2
Order By: Relevance
“…[23][24][25] Insulin is known to decrease the renal excretion of uric acid, 4 and hyperinsulinemia predicts the development of hypertension. 26 We do not have serum insulin levels available at the baseline examination; however, the work of Imazu et al 12 suggests that the relationship between uric acid and the development of hypertension is independent of the insulin level. We were able to control for several elements of the metabolic syndrome, including blood pressure, triglyceride level, glucose level, and central adiposity, but we did not have high-density lipoprotein levels to fully define the presence of Total 892 100…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[23][24][25] Insulin is known to decrease the renal excretion of uric acid, 4 and hyperinsulinemia predicts the development of hypertension. 26 We do not have serum insulin levels available at the baseline examination; however, the work of Imazu et al 12 suggests that the relationship between uric acid and the development of hypertension is independent of the insulin level. We were able to control for several elements of the metabolic syndrome, including blood pressure, triglyceride level, glucose level, and central adiposity, but we did not have high-density lipoprotein levels to fully define the presence of Total 892 100…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have included a significant number of women, 10,12,13 suggesting that the relationship between uric acid and risk for hypertension is present in both men and women. Relying on the measurement of the blood pressure at a single visit necessarily was a source of some misclassification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Humans with a genetic predisposition to hypertension tend to develop insulin resistance and hyperinsulinemia (2,3). It is suggested that hypertension may be associated with hyperinsulinemia in part via glucose intolerance-induced alterations such as sodium retention, vasculopathy, and nephropathy (4). Therefore, ARA on insulin sensitivity have been conflicting, with some studies showing no influence on insulin sensitivity (10)(11)(12) and others demonstrating an improvement of insulin sensitivity (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%